Potential involvement of IL-9 and Th9 cells in the pathogenesis of rheumatoid arthritis. (15th July 2015) - Ciccia, Francesco; Guggino, Giuliana; Rizzo, Aroldo; Manzo, Antonio; Vitolo, Barbara; La Manna, Marco Pio; Giardina, Giuseppina; Sireci, Guido; Dieli, Francesco; Montecucco, Carlo Maurizio; Alessandro, Riccardo; Triolo, Giovanni
Abstract: Objective. IL-9 has been shown to be upregulated before the clinical onset of articular disease in RA. The exact role of IL-9 and Th9 cells in RA, however, has not yet been adequately studied. The aim of this study was to evaluate the expression of IL-9 and IL-9-expressing cells in RA patients. Methods. IL-9, IL-9R, PU.1, IL-9, thymic stromal lymphopoietin (TSLP), IL-4 and TGF-β expression was assessed by real-time-PCR in the synovial tissues of RA and OA patients. IL-9, IL-9R, IL-4, TSLP and TGF-β were also investigated by immunohistochemistry. Peripheral CD4 + T cell subsets were studied by flow cytometry analysis before and after incubation with citrullinated peptides. Results. IL-9 was overexpressed in RA synovial tissues and correlated with the degree of histological organization of B and T cells in ectopic lymphoid structures. The majority of IL-9-producing cells were identified as CD3 + cells. Increased mRNA and protein expression of IL-9R, IL-4, TSLP and TGF-β was also observed in RA synovial tissue. Blood peripheral Th9 cells were expanded by citrullinated peptides. Conclusion. These results indicate that Th9 cells and IL-9 were frequently detected in peripheral blood mononuclear cells and synovia of RA patients. A possible pathogenic role for Th9 in RA is discussed.